(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
The general background the financial statements of cooperatives are essential for transparent and accountable operations, particularly in non-public entities like Savings and Loans Cooperatives. Specific background the Savings and Loans Cooperative (KSP) "BAHAGIA" has been operating since 1980, but the application of SAK ETAP (Financial Accounting Standards for Entities Without Public Accountability) in its financial reporting remains incomplete, particularly in its notes to financial statements and cash flow presentation. Knowledge gap while SAK ETAP provides a standardized framework, many cooperatives, including KSP "BAHAGIA," struggle to fully implement it due to a lack of understanding and technical capacity. This study aims to analyze the extent to which SAK ETAP is applied in KSP "BAHAGIA"’s financial reports, identify gaps in compliance, and offer recommendations for improvement. Results the findings reveal that while KSP "BAHAGIA" adheres to some SAK ETAP requirements, such as balance sheets and income statements, significant discrepancies exist in the notes to financial statements and the exclusion of investment property in cash flow reports. Novelty this research highlights a critical gap in financial reporting for non-public cooperatives, emphasizing the need for targeted education and training for cooperative management in SAK ETAP compliance. Implications the study’s recommendations can help KSP "BAHAGIA" and similar cooperatives improve financial transparency, ultimately enhancing member trust and cooperative governance. Highlights: • Incomplete SAK ETAP implementation affects financial transparency in cooperatives. • Key discrepancies found in notes to financial statements and cash flow reporting. • Improved SAK ETAP education for cooperative management is crucial for compliance. Keywords: Financial Reporting, Cooperatives, SAK ETAP, Non-Public Entities, Compliance